Juifs d'Istanbul, territorialités d'une communauté entre recompositions et dislocations - Yoann Morvan (EchoGéo)
Since more than seven centuries, Jews are in Istanbul. The origins and locations of the community, quite homogeneous from the time of Ottoman Empire, become more complex through twentieth century. Nowadays, behind an apparent optimism, the situation of the Jewish minority is more and more worrying because of internal and external reasons: attacks increase of anti-Semitism and political and geopolitical contexts damage the confidence; in the same time the community’s cohesion is breaking down due to urban sprawl. Based on a fieldwork from the different synagogues of the city (august 2009/april 2011, with more than one hundred people interrogated) this paper retraces the urban trajectories of the Jewish community of Istanbul in order to show its spatial and social perspectives.